Detail of supporting brackets - Ghosh, Ayan (Jio Institute, 2023)
Detail of brackets inside the BMC building. These were inspired from Hindu temple architecture. The amalgamation of Hindu and Islamic architectural details with the overall Gothic style was a delicate and gradual process which Frederick Stevens successfully managed to balance, thereby guaranteeing his pre-eminence in this style during the zenith of Bombay Gothic architecture.